AAV-Delivered Tulp1 Supplementation Therapy Targeting Photoreceptors Provides Minimal Benefit in Tulp1−/− Retinas - Palfi, Arpad; Yesmambetov, Adlet; Millington-Ward, Sophia; Shortall, Ciara; Humphries, Pete; Kenna, Paul F.; Chadderton, Naomi; Farrar, G. Jane (Frontiers in Neuroscience, 2020)
With marketing approval of the first ocular gene therapy and other gene-therapies in clinical trial, treatments for inherited retinal degenerations (IRDs) have become a reality. Biallelic mutations in the tubby like protein 1 gene (TULP1) are causative of IRDs in humans; a mouse knock-out model (Tulp1-/-) is characterized by a similar disease phenotype. We developed a Tulp1 supplementation therapy for Tulp1-/- mice. Utilising subretinal AAV2/5 delivery at postnatal day (p)2-3 and rhodopsin-kinase promoter (GRK1P) we targeted Tulp1 to photoreceptor cells exploring three doses, 2.2E9, 3.7E8 and 1.2E8 vgs. Tulp1 mRNA and TULP1 protein were assessed by RT-qPCR, western blot and immunocytochemistry, and visual function by electroretinography (ERG). Our results indicate that TULP1 was expressed in photoreceptors; the achieved levels of Tulp1 mRNA and protein were similar to wild type levels at p20. However, the thickness of the outer nuclear layer did not improve in treated Tulp1-/- mice. There was a small and transient ERG benefit in the treated retinas at 4 weeks of age (not observed by 6 weeks) when using 3.7E8vg dose. Maximal a- and b-wave amplitudes were 24.3±13.5 µV and 52.2±31.7 µV (n=8) in treated Tulp1-/- mice, which were significantly different (p<0.001, t-test), from the amplitudes detected in untreated eyes (7.1±7.0 µV and 9.4±15.1 µV, respectively; n=16). Our results indicate that Tulp1 supplementation in photoreceptors may not be sufficient to provide robust benefit in Tulp1-/- mice. As such, further studies are required to fine tune the Tulp1 supplementation therapy, which, in principle, should rescue the Tulp1-/- phenotype.